A Giuseppe Dessí. Lettere editoriali e altra corrispondenza Con un'appendice di lettere inedite a cura di Monica Graceffa - Nencioni, Francesca (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2012)
This volume completes the valuable work of cataloguing carried out on the correspondence of Giuseppe Dessí conserved in the 'Alessandro Bonsanti' contemporary archive of Florence. The research, launched by Chiara Andrei in 2003 with the edition of the Corrispondenze familiari (Firenze University Press) and continued in 2009 by Francesca Nencioni with the publication of Lettere di amici e lettori (Firenze University Press), has its third result in this work by Francesca Nencioni, who has indexed the unpublished editorial and professional material, providing it with exhaustive references. The letters make it possible to trace a profile of the writer from his youth through to the 70s, illustrating the historic, political and cultural backdrop against which the events and activities of both his first and second profession developed. This casts light not only his complex professional career, but also on Dessí's collaboration with newspapers and journals, his relations with publishers and his contacts with the world of the mass media. Of particular importance is the appendix of unpublished letters, meticulously edited by Monica Graceffa, comprising the correspondence with two seminal journals of the 1930s and 40s «L'Orto» and «Primato». In the background are the figures of Bottai and Vecchietti and the complex coexistence between the intellectuals of the time and the regime.